Establishment of the bacterial fecal community during the first month of life in Brazilian newborns (Clinics, 2012)
OBJECTIVE: The establishment of the intestinal microbiota in newborns is a critical period with possible long-term consequences for human health. In this research, the development of the fecal microbiota of a group of exclusively breastfed neonates living in low socio-economic conditions in the city of São Paulo, Brazil, during the first month of life, was studied. METHODS: Fecal samples were collected from ten neonates on the second, seventh, and 30th days after birth. One of the neonates underwent antibiotic therapy. Molecular techniques were used for analysis; DNA was extracted from the samples, and 16S rRNA libraries were sequenced and phylogenetically analyzed after construction. A real-time polymerase chain reaction (PCR) was performed on the samples taken from the 30th day to amplify DNA from Bifidobacterium sp. RESULTS: The primary phylogenetic groups identified in the samples were Escherichia and Clostridium. Staphylococcus was identified at a low rate. Bifidobacterium sp. was detected in all of the samples collected on the 30th day. In the child who received antibiotics, a reduction in anaerobes and Escherichia, which was associated with an overgrowth of Klebsiella, was observed throughout the experimental period. CONCLUSION: The observed pattern of Escherichia predominance and reduced Staphylococcus colonization is in contrast with the patterns observed in neonates living in developed countries.